ANALISIS ASOSIASI LOVE OF MONEY, IKLIM ETIS ORGANISASI DAN SPIRITUALITAS TERHADAP EARNINGS MANAGEMENT MOTIVATION - Nurdiana Kus Hartatik; Endah Susilowati (Behavioral Accounting Journal, 2018)
This study aims to examine the effect of love of money, the organizational climate and workplace spirituality on earnings management conducted by middle and lower level managers in the animal feed processing industry in the East Java region. This study discusses manager’s confidence to do earnings management when in high or low organizational ethical conditions, high or low love of money, and high or low spiritual levels. The results of data analysis processed using PLS 3.0 show that the level of love of money affects managers' confidence to do earnings management, the level of organizational ethical climate does not affect managers' confidence to do earnings management and the spiritual level has a positive effect on managers' confidence in earnings management.